PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STUKTURAL PAIR CHECK UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VIII-9 SMP NEGERI 8 PEKANBARU - Halimirnawati Halimirnawati; Rini Dian Anggraini; Syarifah Nur Siregar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
AbstractThe research was classroom action research that aims to improve mathematics learning outcomes with applied the cooperative learning pair check structural approach. The subject of the research is students of class VIII-9 SMP Negeri 8 Pekanbaru in the first semester academic years 2013/2014. There are 32 students in the class, consist of 13 boys and 19 girls who have heterogeneous academic ability. The research are two cycles, each a cycle has four stages, that are planning, implementation, observation, and reflection. Each end of the cycle of daily tests carried out. Data collected through observation and tests in the form of daily tests. Data analysis was performed with analysis of descriptive narrative and descriptive statistical analysis. The action is successful if the number of students who achieve a score of minimum mastery criteria increase in daily tests I and II. The number of students who achieve a score of minimum mastery criteria on basic, daily test I (first cycle) and daily test II (second cycle) are respectively 40.63%, 68.75%, dan 87.5%. Minimum mastery criteria attainment percentage indicates that the cooperative learning cooperative learning pair check structural approach can improve students' mathematics learning outcomes math class VIII-9 SMP Negeri 8 Pekanbaru.Key words: Mathematics learning outcome, Cooperative learning, Pair Check, Class action research